2018
DOI: 10.1002/suco.201700288
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich panels with folded plate and doubly curved UHPFRC facings

Abstract: Sandwich‐structured composites represent an efficient method to establish building envelopes which concurrently satisfy several demands. Besides low self‐weight with high load‐bearing capacity, sandwich panels provide sufficient physical properties, such as heat and sound insulation. In general, sandwich panels for applications in building industry are made of flat or thin profiled metal sheets or thick concrete facings. However, standard elements are limited to short spans. In contrast, spatially shaped concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
0
12
0
6
Order By: Relevance
“…It is beneficial to use reinforced high strain‐hardening UHPC in structures with high demand of crack width control. Stark et al applies UHPC to design long‐span sandwich structures, which utilize high strength and high ductility to significantly increase the load carrying capacity of the sandwich unit. During a research project, Zani conducted several experimental tests to mechanically identify the individual and coupling materials that make up the innovative multilayer roof slab; experiments have shown that UHPC materials can improve the toughness and ductility of common materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is beneficial to use reinforced high strain‐hardening UHPC in structures with high demand of crack width control. Stark et al applies UHPC to design long‐span sandwich structures, which utilize high strength and high ductility to significantly increase the load carrying capacity of the sandwich unit. During a research project, Zani conducted several experimental tests to mechanically identify the individual and coupling materials that make up the innovative multilayer roof slab; experiments have shown that UHPC materials can improve the toughness and ductility of common materials.…”
Section: Introductionmentioning
confidence: 99%
“…Der Verbund zwischen Betondeckschichten und Kernmaterial kann durch das Einschäumen eines PUR‐Dämmstoffs anstelle herkömmlicher Herstellungsmethoden mit vorkonfektionierten Blockschäumen erheblich verbessert werden [14–16]. Nachdem bereits in [17] die Ausschäumtechnik an maximal 4 m spannenden Elementen ohne Verbundmittel erfolgreich erprobt wurde, wird im vorgestellten Projekt die Übertragbarkeit der Technik auf großformatige Elemente mit 8 m Länge überprüft. Hierbei werden außerdem linienförmige Verbundmittel aus alkaliresistentem (AR‐) Glas verwendet, welche die Sandwichtragwirkung der Elemente und den Verbund zwischen Kern und Deckschichten verbessern.…”
Section: Einleitung Und Motivationunclassified
“…Nach dem Rütteln erhärtet das Wandsystem in einem Trockenofen, wodurch die Halbfertigteile bereits nach acht Stunden ausgeschalt werden können. Nach dem Aufstellen der Wände auf der Baustelle wird der Kern mit Ortbeton vergossen, sodass der Gesamtquerschnitt nach Erhärten des Betons monolithisch trägt .…”
Section: Entwicklung Des Konzepts Des Stabankersunclassified